2016
DOI: 10.1111/adb.12457
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for GABA‐A receptor dysregulation in gambling disorder: correlation with impulsivity

Abstract: As a behavioural addiction, gambling disorder (GD) provides an opportunity to characterize addictive processes without the potentially confounding effects of chronic excessive drug and alcohol exposure. Impulsivity is an established precursor to such addictive behaviours, and GD is associated with greater impulsivity. There is also evidence of GABAergic dysregulation in substance addiction and in impulsivity. This study therefore investigated GABAA receptor availability in 15 individuals with GD and 19 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…Sleep inductors regulate sleep cycles through sedative interactions with GABA receptors located in the cerebral cortex, thalamus, and hypothalamus (Szabadi, ). A recent study reported evidence that GABAergic dysregulation is correlated with impulsivity, supporting claims of previous studies that suggest an association between increased impulsivity and GABA modulating drugs, such as benzodiazepines (Hayes et al., ; Mick et al., ). We also observed a specific association of dopaminergics, antidepressants, and MAOBIs with QUIP‐RS items related with eating behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…Sleep inductors regulate sleep cycles through sedative interactions with GABA receptors located in the cerebral cortex, thalamus, and hypothalamus (Szabadi, ). A recent study reported evidence that GABAergic dysregulation is correlated with impulsivity, supporting claims of previous studies that suggest an association between increased impulsivity and GABA modulating drugs, such as benzodiazepines (Hayes et al., ; Mick et al., ). We also observed a specific association of dopaminergics, antidepressants, and MAOBIs with QUIP‐RS items related with eating behaviors.…”
Section: Discussionsupporting
confidence: 64%
“…A prominent role of dysfunctional GABA neurotransmission in addiction has been suggested by recent studies with [ 11 C]Ro15‐4513 PET in individuals suffering from addiction. Alcohol (Lingford‐Hughes et al, ) and opiate (Lingford‐Hughes et al, ) addiction were linked to lower levels of GABA‐A receptor availability in limbic regions, compared to controls, while gambling addiction (Mick et al, ) and a history of cigarette smoking (Stokes et al, ) were associated with higher levels of limbic GABA‐A receptor availability compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the hypothesis by challenging participants with oral L‐dopa to increase their brain dopamine and used [ 11 C]Ro15‐4513 PET, a marker of GABA A /BDZ receptor availability, to detect increases in synaptic GABA levels. A number of recent PET‐studies using the [ 11 C]Ro15‐4513 ligand point to a prominent role of altered GABA neurotransmission in individuals addicted to alcohol (Lingford‐Hughes et al, ), opiates (Lingford‐Hughes et al, ), nicotine (Stokes et al, ), and gambling (Mick et al, ). To our knowledge, our study is the first to directly examine altered GABA regulation by exogenous dopamine as evidenced by GABA‐A receptor availbility in a nondrug addictive disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropharmacological evidence also supports such an explanation. Indeed, cerebral responses to probabilistic outcomes have been found to be modulated by dopaminergic circuits in the midbrain that can be activated by changes in the GABA A receptor system [35]. Given the action of BZs on GABA A receptors, BZs may reduce inhibitory control and influence sensitivity to reward and punishment, eventually leading to deregulated gambling behaviours as suggested by psychopharmacological models of problem gambling [36].…”
Section: Discussionmentioning
confidence: 99%